The economic feasibility of crane cabins with real-time computer-aided visual guidance system - Dondur, Nikola; Spasojević-Brkić, Vesna K; Brkić, Aleksandar; Perišić, Martina (Serbian Journal of Management, 2020)
Cranes’ operations are extremely risky and hazardous tasks, as demonstrated in various surveys in the field of incidents’ causes and effects. The most frequent cause of unsafe crane operation task execution is human error. Accordingly, innovation which enables cranes’ safe operations, prevents “blind lifts” and helps crane operator to avoid potential error is urgent. Project SPRINCE has proposed computer-aided Visual Guidance System as a real time solution aimed to prevent crane accidents, caused by obstructed view. This paper analyses the economic feasibility of Visual Guidance System application in various scenarios in aim to connect human, technology and organization issues through cost-benefit framework. There are two proposed investment scenarios analysed: A) Producing and selling of crane cabins with real-time computer-aided Visual Guidance System and B) Usage (purchase) of crane cabins with real-time computer-aided Visual Guidance System. The economic appraisal has proved that the total economic benefit in both scenarios in the complete utilization period is several times higher than the buying price, while the internal rate of return is few times higher than the aggregate rate of interest paid. Also, the amount of time which takes to recover the cost of an investment is less than four years. Moreover, both scenarios belong to the category of innovation projects with very low risk.